Penyelamatan reputasi lingkungan hidup melalui Pengolahan limbah ampas tahu menjadi tepung, di Desa Ketangi, Kab. Malang - Azahra, Dila Fitri (Maliki Interdisciplinary Journal, 2024)
This article will discuss one of the potentials for improving the economy of the people of Ketangi Village, Malang Regency, in the form of a tofu home industry whose processing is still traditional and produces liquid waste as well as solid waste. Household-scale tofu factories (home industry) often do not handle the waste disposal process properly and are not equipped with proper waste processing, as is the case with factories in the Ketangi area, where waste management, especially solid waste (tofu dregs), has not been implemented properly. done to the maximum. Tofu dregs are only bought and sold at very low prices. So, the ingredients in tofu are not utilized properly, even though the protein value in tofu is quite high. The aim of this research is to determine the use of tofu dreg waste, which is managed into food. The method used in this research is the ABCD (asset-based community-driven development) method, which is a method that prioritizes the benefits of assets and potential that exist in the village and are owned by the community. The source of the data obtained is the result of interviews and documentation with sources, namely tofu producers. The research results show that tofu waste is not just community waste that is thrown away but can be reprocessed into food.